Mathematical Analysis of Overtourism and Carrying Capacity in Bali Tourism Using a Logistics Growth Model - Asyifa, Melia Sukma; Liestiandre, Hanugerah Kristiono; Muhammad Salim, Muhammad Arfin (Ann Publisher, 2026)
Background. The growth of tourism in Bali has become a complex and multidimensional phenomenon, where the increase in tourist numbers has a significant economic impact but also triggers environmental, social, and cultural pressures. Overtourism occurs when the number of tourists exceeds a destination's carrying capacity, creating an imbalance in the system. Empirical studies show that the post-pandemic surge in tourism has a positive economic impact but also increases pressure on the environment and infrastructure. Aims. This research develops a dynamic logistics growth-based mathematical model to explain the relationship between the number of tourists and the capacity to accommodate in Bali's tourism system. The model is formulated as a nonlinear differential system in which capacity is treated as a time variable. Results. The results of the analysis show that carrying capacity is dynamic and degrades as tourist pressure accumulates. Conclusion. This study introduces the concept of effective capacity and shows that overtourism is an endogenous phenomenon in the tourism system.